Al Jazeera: Between Islamic Journalism and Islamic Da'wah - Efendi Rahmat; Cecep Suryana (Jurnal Iman dan Spiritualitas, 2026)
This research focuses on Al Jazeera's role as a global media outlet at the intersection of modern journalistic practices and Islamic da'wah values. As a pioneer of press freedom in the Arab world, Al Jazeera serves not only as a conveyor of information but also as a normative actor, framing Islamic, political, and humanitarian issues from a perspective considered more inclusive and just. This raises critical questions about the extent to which its journalistic practices truly represent Islamic da'wah values or merely follow international journalistic norms. The purpose of this research is to identify Al Jazeera's journalistic characteristics rooted in Islamic principles, explore the role of da'wah in its reporting, and examine the tension between the media's demands for objectivity and its moral mission. The method employed is a qualitative approach, utilising case studies, which involve analysing news content and discussion programs on Al Jazeera. The research also utilizes secondary data from relevant academic literature. Discourse analysis techniques are applied to explore how this media outlet frames important issues and how global audiences respond to the narratives it constructs. The research results demonstrate that Al Jazeera effectively integrates the idealism of da'wah (Islamic preaching) with journalistic professionalism. Nevertheless, the media outlet continues to face significant challenges, including geopolitical pressure and accusations of bias. This synergy between moral mission and professional standards makes Al Jazeera not only a source of information but also a global educational instrument that plays a vital role in shaping international public opinion.